Menikmati “Tanda” Dakwah Islam dalam Film Dokudrama-Biopik: Sang Kyai - Ahmad Jum’a Khatib Nur Ali (Tsaqofah, 2015)
Biopic film is one of documentary film genre. This article discusses Sang Kyai a biopic film not only as interpretation of KH. Hasyim Asy’ari biographical history, but also as “ulama” that struggle against colonialism in Indonesia. The article shows, drama element in biopic film Sang Kyai can be used to presents “Islamic da’wah” message, Islam “rahmatan lil ‘aalamiin”.